Pengaruh Islamic Corporate Social Responsibility (ICSR) Terhadap Kinerja Keuangan Perbankan Syariah Periode 2016-2022 (Studi Pada Bank Umum Syariah Menggunakan Index ISR) - Faradiz, Elvin Nur; Ningrum, Ririn Tri Puspita; Mahfudhotin, Mahfudhotin (WADIAH, 2024)
Islamic Corporate Social Responsibility (ICSR) is a corporate social responsibility that must be carried out by the company where the company is established and will then be presented in the company's annual report. The formulation of the problem in this study is how is ICSR at Islamic Commercial Banks (BUS), how is Financial Performance at BUS. The results of this study based on the t test or hypothesis test obtained a probability value of 0.034,. The criteria for the t test are the probability value < 0.05. In the correlation analysis, a Pearson correlation value of -0.272 is obtained with a significant value of 0.034 <0.05, which means that there is a correlation between the Islamic Corporate Social Responsibility (X) variable and financial performance which is low and significant and a negative sign means the relationship is in the opposite direction, if ICSR increases, financial performance will decrease, and vice versa., it can be concluded that Ho is rejected and Ha is accepted, which means that there is a negative and significant effect of the ICSR variable on the financial performance of Islamic banking for the 2016-2022 period.